ELTV Week-in-Review (African Knowledges and the History Publication since the 1970s)
Summarizes major events of the past week with commercials from DHL, Ovaltine, Liberia Telecommunications Corporation, Iter Pharmacy, Zambia Airways.
Keywords: News